Synthesis and Antifungal Activity of Pyrimidine Derivatives Containing an Amide Moiety - Wu, Wenneng; Lan, Wenjun; Wu, Chenyan; Fei, Qiang (Frontiers in Chemistry, 2021)
In this study, 17 novel pyrimidine derivatives containing an amide moiety were synthesized. Then their in vitro antifungal activities against Botryosphaeria dothidea (B. dothidea), Phomopsis sp., and Botrytis cinereal (B. cinereal) were determined. A preliminary biological test showed that compounds 5-bromo-2-fluoro-N-(2-((2-methyl-6-(trifluoromethyl)pyrimidin-4-yl)oxy)phenyl)benzamide (5f) and 5-bromo-2-fluoro-N-(3-((2-methyl-6-(trifluoromethyl)pyrimidin-4-yl)oxy)phenyl)benzamide (5o) exhibited higher antifungal activity against Phomopsis sp., with an inhibition rate of 100% compared to that of Pyrimethanil at 85.1%. In particular, compound 5o exhibited excellent antifungal activity against Phompsis sp., with the EC50 value of 10.5 μg/ml, which was even better than that of Pyrimethanil (32.1 μg/ml). As far as we know, this is the first report on the antifungal activities against B. dothidea, Phomopsis sp., and B. cinereal of this series of pyrimidine derivatives containing an amide moiety.